Analisis Risiko Kebangkrutan Menggunakan Model Altman Z-Score: Studi Kasus PT Kereta Api Indonesia Periode 2017-2022 - Putri, Errica A; Sulistiyo, Hari (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study analyzes the bankruptcy risk of PT Kereta Api Indonesia during the 2017-2022 period using the Altman Z-Score model. The data consists of the company’s annual financial statements, which were examined through the calculation of financial ratios as components of the Z-Score. The Z-Score values were used to assess the company’s financial health and estimate its potential bankruptcy risk. Analysis results indicate that in 2017, the company was in a financially healthy condition with a Z-Score of 2.67. The score declined in 2018 and 2019, placing the company in the gray area with values of 2.05 and 1.59, respectively. In 2020 and 2021, the company fell into the distress zone with Z-Scores of 0.57 and 0.93, reflecting a high risk of bankruptcy driven by financial pressure from the Covid-19 pandemic. In 2022, the company showed signs of recovery with a Z-Score of 1.77, returning to the gray area. The decline in financial performance was influenced by a combination of external pressures and suboptimal internal efficiency. This study provides a comprehensive overview of the financial condition of PT Kereta Api Indonesia and may serve as a foundation for formulating long-term financial strengthening strategies.